Assessment of Knowledge, Attitude, and Practice in the General Population Regarding Hypertension: A Cross-Sectional Study from Iran - Fariba Lookian; Elliyeh Ghadrdan; Maryam Mousavi (Research Center for Rational Use of Drugs (RCRUD), 2019)
Background: Patients' knowledge, attitude, and practice are essential factors for hypertension management. Therefore, the information that reflects the level of public awareness can affect health policies. The aim of this study is to assess the knowledge, attitude, and practice of the general population about different aspects of hypertension.  Method: In this pilot study, we totally include 198 adults with or without hypertension who came to the main teaching hospital in Mashhad city. Patients were randomly selected, and they filled a KAP questionnaire.  Results: Most of the participants were younger than 30 years old. The gender distribution consisted of 53.7% males and 45.8% females. The educational levels of participants were 13.8% primary or less, 33% secondary-tertiary and 53.2% academic. Severe headache and dizziness were the principal hypertension symptoms in participant perspectives. Most of the people had reported that salt intake and fatty foods may cause hypertension more than others. Majority of the responders considered low salt-fat diet and regular exercise were the main hypertension prevention. In the present study, participants believed that all the population can be at risk of hypertension, except primary or less educated who said low exercise and positive family history are the main causes.  All groups believed that hypertension risks are threatening both individual and society. In the presence of hypertension symptoms, referring to the nephrologist for initial evaluation was a priority for thirty percent of responders. Conclusions: Our study concluded that the majority of the general population had good knowledge about hypertension. We found that attitude was satisfied, although the inappropriate practice was seen in participants.